2012
DOI: 10.1186/1471-2407-12-48
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-initiating cells derived from established cervical cell lines exhibit stem-cell markers and increased radioresistance

Abstract: BackgroundCancer-initiating cells (CICs) are proposed to be responsible for the generation of metastasis and resistance to therapy. Accumulating evidences indicates CICs are found among different human cancers and cell lines derived from them. Few studies address the characteristics of CICs in cervical cancer. We identify biological features of CICs from four of the best-know human cell lines from uterine cervix tumors. (HeLa, SiHa, Ca Ski, C-4 I).MethodsCells were cultured as spheres under stem-cell condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
154
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(173 citation statements)
references
References 48 publications
17
154
0
Order By: Relevance
“…The identification of uterine cervical epithelial stem cells has been reported in cervical lesions and cancer cell lines (9,10); these studies, however, did not elucidate the role of HPV, an essential etiologic agent for the development of cervical cancer, particularly in exacerbating malignant progression and stemness properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification of uterine cervical epithelial stem cells has been reported in cervical lesions and cancer cell lines (9,10); these studies, however, did not elucidate the role of HPV, an essential etiologic agent for the development of cervical cancer, particularly in exacerbating malignant progression and stemness properties.…”
Section: Discussionmentioning
confidence: 99%
“…Reports suggest preferential physical interaction of the virus with squamocolumnar junction (SCJ) in TZ that forms basal/reserve cells with stem cell properties (8). These observations along with technological advancements in identification of CSCs using established phenotypic and functional markers have facilitated identification and characterization of cervical CSCs from primary tumors (7,9) and cervical cancer cell lines (10). The cell lines, SiHa (HPV16 þ ) and HeLa (HPV18 þ ) constitutively express markers that closely resemble SCJ cells (8) thus making them a suitable experimental model for investigation of cervical CSCs in greater detail.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, targeting one antigen alone is unlikely to generate effective antitumor immune responses to mediate tumor rejection because of rapid appearance of escape mutants and the general inefficiency of monovalent cancer vaccines (Buonaguro et al, 2011;Durrant et al, 2011). Interestingly, it was found that cancer stem cells (CSCs) and embryonic stem cells (ESCs) shared similar cell surface markers and antigens not presented by adult tissues, which played a part in metastasis, angiogenesis and increased chemoradiotherapy resistance in cancer (Field et al, 2010;Kee et al, 2012;Lopez et al, 2012), so immune response against ESCs…”
Section: Introductionmentioning
confidence: 99%
“…Tumor spheres were prepared as previously described. 51 In brief, cells were detached with EDTA (Life Technologies, Carlsbad, CA, USA), washed with PBS and placed in serum-free medium mixed with 20 ng/ ml epidermal growth factor (EGF PHG0311L, Life Technologies), 20 ng/ml basic fibroblast growth factor (bFGF PHG0021, Life Technologies) and 0.4% bovine serum albumin (BSA, Sigma-Aldrich) at a density of 1 Â 10 3 cells/ml and cultured in ultra-low attachment plates (CLS3473 Costar, Sigma-Aldrich). The sphere culture medium was changed every 48 h until the majority of spheres reached 300-400 mm in diameter.…”
Section: Discussionmentioning
confidence: 99%